Perencanaan dan Perancangan Daycare di Kota Denpasar - I Putu Sidharta Nanda Kusuma; I Nyoman Warnata; I Wayan Widanan (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2022)
Daycare is an alternative service that can be used by parents who work as an institution that can temporarily replace as long as the parents work in terms of care, protection and also the provision of guidance to the child. Childhood at an early age is a time full of unique and important events that lay the foundation for a person in adulthood. From the beginning, children must be ensured to receive good and appropriate guidance so that the development period is passed gradually and continuously. Parents should give their child sufficient attention and supervision. However, the demands of life are getting higher, making mothers participate in making a living or have a desire for a career. Basically, leaving the child in the daycare will be very helpful, not only for the parents, but also for the child himself. By leaving children in daycare, parents will have more time to carry out daily activities (work) with a safe feeling that the child is still there to take care of, maintain, and care, and for the child himself the daycare is used as a place to interact and train independence so that children do not always depend on parents in their daily lives. Based on the existing problems and potentials, in improving the quality of early childhood care in Denpasar City, therefore it is proposed that Daycare Planning and Design in Denpasar City.